Interleukin-2 gene therapy of surgical minimal residual tumour disease - Vlk, V; Rössner, P; Indrová, M; Bubeník, J; Sobota, V (International journal of cancer, 1998)
Our study was designed to examine the effects of IL-2 gene therapy in a surgical minimal residual tumour disease (SMRTD). Mice were inoculated s.c. with methylcholanthrene (MC)-induced MC12 sarcoma cells. When the tumours reached 8 to 12 mm in diameter, they were excised, either completely ("microscopic SMRTD") or incompletely ("macroscopic SMRTD"). On day 90 after surgery, the tumour recurrence rate in untreated mice with microscopic SMRTD was approximately 30%, whereas in those with macroscopic SMRTD it was 75%. After surgery, experimental mice were treated with 2 types of irradiated, IL-2 gene-modified, IL-2-producing tumour cell vaccine. One type of vaccine was derived from the MC12 sarcoma cells (MC12-1L2/IV-3); the other type was derived from an unrelated X63-Ag8.653 plasmacytoma (X63-m-IL-2). Both types of vaccine failed to cure the macroscopic SMRTD. Whereas the X63-m-IL-2 vaccine was also ineffective in the microscopic SMRTD, the MC12-IL2/IV-3 vaccine was capable of preventing growth in all but one mouse (1164) with microscopic SMRTD when administered 2 to 5 days after surgery. If the vaccination took place 2 days before surgery or later than 5 days after surgery, the therapeutic activity was lost. Vaccination with irradiated parental MC12 cells did not produce any significant benefit compared to the operated-only mice. The protective effect of the MC12-L2/IV-3 vaccine was specific and comparatively long-lasting. Vaccinated mice, which had rejected the MC12 tumour residuum, were capable of rejecting a second inoculum of the MC12 sarcoma cells injected on days 35 to 110 after surgery but succumbed to the growth of 2 other unrelated murine sarcomas carrying different tumour-rejection antigens.
Keywords: Interleukin-2; Immunologic Memory; podskupiny lymfocytů; reziduální nádor; počet lymfocytů; Genetic Therapy; Methylcholanthrene; transfekce; myši inbrední C57BL; Neoplasm, Residual; genetická terapie; Lymphocyte Subsets; Vaccination; Mice; vakcinace; Lymphocyte Count; interleukin-2; experimentální sarkom; zvířata; methylcholanthren; Transfection; myši; Sarcoma, Experimental; imunologická paměť; Mice, Inbred C57BL; Animals